CT Findings of Patients with Small Bowel Obstruction due to Bezoar: A Descriptive Study - Fatih Altintoprak; Bumin Degirmenci; Enis Dikicier; Guner Cakmak; Taner Kivilcim; Gokhan Akbulut; Osman Nuri Dilek; Yasemin Gunduz (The Scientific World Journal)
Purpose. The aim of this study was to present the computed tomography (CT) findings of bezoars that cause obstruction in the small bowel and to emphasize that some CT findings can be considered specific to some bezoar types. Materials and Methods. The records of 39 patients who underwent preoperative abdominal CT and subsequent operation with a diagnosis of intestinal obstruction due to bezoars were retrospectively analyzed. Results. In total, 56 bezoars were surgically removed from 39 patients. Bezoars were most commonly located in the jejunum (n=26/56, 46.4%). Sixteen (41.0%) patients had multiple bezoar locations in the gastrointestinal tract. Common CT findings in all patients were a mottled gas pattern and a focal ovoid or round intraluminal mass with regular margins and a heterogeneous internal structure. Furthermore, some CT findings were determined to be specific to bezoars caused by persimmons. Conclusions. Preoperative CT is valuable in patients admitted with signs of intestinal obstruction in geographic regions with a high bezoar prevalence. We believe that the correct diagnosis of bezoars and the identification of their number and location provide a great advantage for all physicians and surgeons. In addition, some types of bezoars have unique CT findings, and we believe that these findings may help to establish a diagnosis.